Late Mesozoic marine Antarctic fishes: future perspectives based on the newly collections recovered in the Ameghino and López de Bertodano Formations - Gouiric Cavalli, Soledad (2017)
Fil: Gouiric Cavalli, Soledad. Consejo Nacional de Investigaciones Científicas y Técnicas. Buenos Aires, Argentina.